SKEPTISME PROFESIONAL SEBAGAI VARIABEL PEMODERASI PENGARUH TEKANAN KETAATAN DAN PENGALAMAN AUDITOR PADA AUDIT JUDGMENT - Parastika, Ni Putu Eka; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2017)
Professional skepticism is very important for auditor to obtain solid information, which will be the basis of relevant audit evidence to support the supply of opinion on the fairness of the financial statements. This study aims to prove empirically Professional Skepticism As moderating variables Obedience Pressure Effect and Experience Auditor Audit on Judgment. This research was conducted in the public accounting firm in Bali, Number of samples taken by 62 auditors. Samples selection by purposive sampling method, the sampling technique using specific criteria. Collecting the data by distributing questionnaires. The analysis technique used is variable Moderating Interaction Test (Moderated Regression Analysis). Based on the analysis by MRA (Moderated Regression Analysis) showed the entire hypothesis is accepted that pressure observance negatively affected the audit judgment, auditor's experience as positive effect on audit judgment, skepticism professional weaken the influence of stress adherence to the audit judgment, skepticism professionals strengthen the influence auditor's.
Keywords: pressure obedience , auditor' s experience , professional skepticism , audit judgment